The Effectiveness of the International Environmental Law: The Issues of State Sovereignty, National Interests, and Differing Levels of Commitments - Albakjaji , Mohamad; Baroudy, Jinane El (Journal of Ecohumanism, 2024)
This study aims to explore the main challenges facing international environmental law and affecting its effectiveness. Although many international texts and agreements have been adopted to address environmental degradation and promote sustainable resource development, most of these agreements remain ineffective in achieving the objectives of these agreements. The critical study reveals that these legal frameworks face many challenges that affect the effectiveness of these texts, for example, there are issues such as national sovereignty, the lack of unified implementation at the state level, insufficient funding, and weak institutional frameworks. This study aims to provide a comprehensive analytical view of the factors that affect the effectiveness of these texts and frameworks. The issues of national sovereignty, insufficient funding, weak institutional frameworks, different levels of commitment, lack of political will, and global cooperation will be mainly discussed here. By focusing on the most important challenges facing international environmental law, this research aims to contribute to developing international environmental law to make it more effective.